THE RELATIONSHIP BETWEEN ELDERLY KNOWLEDGE ABOUT ORAL HEALTH AND PERIODONTITIS AT POSYANDU KEMUNING REJOSOPINGGIR VILLAGE JOMBANG DISTRICT - Nur Choiryah; Ida Chairanna Mahirawatie; I.G.A. Kusuma Astuti N.P (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2026)
Periodontitis remains a major cause of tooth loss among the elderly, significantly affecting masticatory function, aesthetics, and overall quality of life. Despite its high prevalence, limited awareness and misconceptions about oral health among older adults may contribute to delayed prevention and treatment. Therefore, this study aimed to analyze the relationship between elderly knowledge of oral health and the incidence of periodontitis at the Kemuning Integrated Health Post, Rejosopinggir Village, Jombang Regency. This research employed an analytic observational design with a cross-sectional approach. A total of 32 elderly participants aged ≥60 years were selected using random sampling. Data were collected through a structured questionnaire to assess oral health knowledge and clinical examination using the Russell Periodontal Index to determine periodontal status. Statistical analysis was performed using the chi-square test with a significance level of 0.05. The findings revealed that the majority of respondents had poor knowledge of oral health (78.1%), and most participants exhibited severe periodontal conditions, with an average Russell Periodontal Index score of 3.55. However, the chi-square test indicated no statistically significant relationship between oral health knowledge and the occurrence of periodontitis (p = 0.396 > 0.05). These results suggest that knowledge alone is insufficient to influence periodontal health outcomes. In conclusion, although poor oral health knowledge is prevalent among the elderly, it does not significantly correlate with the incidence of periodontitis in this population. Other factors, such as behavioral habits, access to healthcare services, systemic conditions, and socioeconomic status, may play a more dominant role. Comprehensive and practical oral health interventions are therefore recommended to improve periodontal health among the elderly.